Application of analytic hierarchy process and GIS in landslide vulnerability assessment of Matutinao Watershed, Cebu, Philippines a case study anchored on the climate change framework - Lanuza, Reynaldo L.; Carreon, Bruno O.; Camello, Daisy Luisa S.; Daño, Antonio M. (2015)
The study was conducted in the ecologically and economically significant Matutinao Watershed in Cebu. Ongoing developmental activities in the area ncessitate a landslide vulnerability assessment to avoid possible losses of lives and properties. A GIS-assisted aproach was developed to a) evaluate the utility of GIS with regard to landslide vulnerability assessment anchored on the climate change framework; b) identify and map out the areas vulnerable to landslide; c) recommend appropriate measures to avoid loss of lives and properties; and d) formulate policy recommendations.

Using the Analytical Hierarchy Process (AHP) in determining the relative importance of factors identified and GIS, the landslide vulnerability anchored in a climate change perspective was determined. Exposure to landslide was based on 2020 climate projections. The sensitivity was computed based on the model derived from AHP, expressed as L = 0.8297[0.3160SI + 0.0973R + 0.0973T + 0.0912Ga + 0.0912Gf + 0.1729Gfl + 0.0698So + 0.0633Lu] + 0.1703[0.2532FS + 0.3175H + 0.4349GD].
Keywords: Landslides; Watershed management